Design scheme of linear dispersive space-time codes for downlink multiuser MIMO systems - ZHOU Meng1; ZHANG Can2 (Tongxin xuebao)
A scheme of linear dispersive space-time codes was presented for downlink multiuser MIMO systems under the condition only limited rates could be employed by basestation for transmitting downlink data. The combination optimization problem with respect to the design was deduced, and a suboptimal algorithm with low computational complexity was given. The designed scheme does not require the condition of continuous downlink rates, which was assumed in previous work. Simulations show that the designed scheme has better performance than previous schemes.